Dihydroartemisinin prevents liver fibrosis in bile duct ligated rats by inducing hepatic stellate cell apoptosis through modulating the PI3K/Akt pathway. Issue 3 (10th February 2016) - Chen, Qin; Chen, Lianyun; Wu, Xiafei; Zhang, Feng; Jin, Huanhuan; Lu, Chunfeng; Shao, Jiangjuan; Kong, Desong; Wu, Li; Zheng, Shizhong
Abstract: As a frequent event following chronic insult, liver fibrosis triggers wound healing reactions, with extracellular matrix components accumulated in the liver. During liver fibrogenesis, activation of hepatic stellate cells (HSCs) is the pivotal event. Fibrosis regression can feasibly be treated through pharmacological induction of HSC apoptosis. Herein we showed that dihydroartemisinin (DHA) improved liver histological architecture, decreased hepatic enzyme levels, and inhibited HSCs activation in the fibrotic rat liver. DHA also induced apoptosis of HSCs in such liver, as demonstrated by reduced distribution of α‐SMA‐positive cells and the presence of high number of cleaved‐caspase‐3‐positive cells in vivo, as well as by down‐regulation of Bcl‐2 and up‐regulation of Bax. In addition, in vitro experiments showed that DHA significantly inhibited HSC proliferation and led to dramatic morphological alterations in HSCs. we found that DHA disrupted mitochondrial functions and led to activation of caspase cascades in HSCs. Mechanistic investigations revealed that DHA induced HSC apoptosis through disrupting the phosphoinositide 3‐kinase (PI3K)/Akt pathway and that PI3K specific inhibitor LY294002 mimicked the pro‐apoptotic effect of DHA. DHA is a promising candidate for the prevention and treatment of liver fibrosis. © 2016 IUBMB Life, 68(3):220–231, 2016